Índice de masa corporal asociado a hipotensión arterial en cesáreas con anestesia raquídea en el Hospital Regional Docente de Trujillo 2020-2021 - Muñoz Rivasplata, Lys Thalia (2022)
Hypotension under spinal regional anesthesia is a subject of study and discussion, due to its high incidence. Studies have focused on finding risk factors, studying pathophysiology, creating management and prophylaxis protocols. There are few studies related to the Body Mass Index (BMI) associated with hypotension in caesarean sections, being relevant that, the greater the content in the abdominal cavity, the greater the probability of aorto-caval compression syndrome and the greater risk of hypotension, it is also related to maternal and fetal adverse effects.